Eating Competence and Dietary Intake of Sexual and Gender Minority College Students - Murphy, Sara (Nutrients, 2021)
Sexual and gender minority college students are underrepresented in nutrition research and may face unique challenges related to eating which impact their overall diet quality. We assessed the differences in eating competence and dietary intake between sexual and gender minority (SGM) and cisgender heterosexual (CH) college students. Participants (n = 2645) reported sexual orientation, gender identity and completed the Eating Competence Satter Inventory (ecSI 2.0™ through an online questionnaire. Three-day food records examined dietary intake. Intake was compared to recommendations for nutrients of public health concern. Chi-square and ANCOVA examined differences between eating competence and dietary intake. There were no differences in total ecSI 2.0™ scores. Subscale scores for Eating Attitudes and Contextual Skills were significantly higher in CH vs. SGM students (13.4 ± 0.1 vs. 12.4 ± 0.4 p = 0.01 and 10.7 ± 0.1 vs. 9.9 ± 0.3, p = 0.01, respectively). Most students (40.8%) met one nutrient recommendation. The proportion of students meeting nutrient recommendations were similar for SGM and CH. SGM populations may struggle with attitudes and eating behaviors. Dietary intake of SGM and CH students were similarly inadequate when compared to recommendations.